Comprehensive future projections for the line-shaped convective system associated with Baiu front in Japan under RCP scenarios using regional climate model and pseudo global warming experiments - Naka, Yukari; Nakakita, Eiichi (Frontiers in Earth Science, 2023)
Herein, climate change projections of localized extreme rainfall associated with the Baiu front (Baiu extreme rainfall) are investigated from June to August in Japan under two representative concentration pathway (RCP) scenarios (RCP2.6 and RCP8.5) by analyzing the numerical simulations of a 5-km-mesh high-resolution regional climate model (NHRCM05), which gives us the probabilistic future projections by using ensemble simulations, and by conducting Pseudo Global Warming (PGW) experiments for two typical events (Kameoka heavy rainfall in 2012 and Hiroshima heavy rainfall in 2014) with the cloud-resolving model, which enables us to elucidate the mechanisms of future change. The NHRCM05 analysis revealed that the frequency of Baiu extreme rainfall would increase by 1.2-times under RCP2.6 and by ≥ 1.5-times under RCP8.5 compared with the present climate. Moreover, the maximum total rainfall would increase due to global warming. To elucidate the mechanisms of rainfall intensification, the PGW experimental results were analyzed. 2012-Kameoka PGW analysis revealed that the rainfall increasing rate was almost twofold compared to the theoretical Clausius-Clapeyron scaling, which was attributed to a nonlinear effect of intensification of the back-building dynamical structure by the convergence in the lower level and the strengthening of the updraft, resulting in localization of water vapor into the cumulonimbus that cause much more buoyancy. Meanwhile, 2014-Hiroshima event experiments indicated that the rainfall decreased with global warming due to water vapor consumption in upstream areas. However, the PGW of 2014-Hiroshima possibly happened to show a decreasing trend as further NHRCM05 analysis of events similar to 2014-Hiroshima showed an increasing trend in rainfall. This study highlights the importance of predicting future changes by combining results obtained from various methods, including climate model analysis or PGW, with a profound understanding of the implications and feature of each result as well as the fact that disaster prevention and adaptation measures are urgently needed.